The Effect of Giving Warm Compresses on Pain in First Stage Inpartu Patients at Kotamobagu Regional Hospital - In Novalita; Anik Sri Purwanti; Widia Shofa Ilmiah (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Labor pain in the first stage is one of the main challenges faced by mothers in labor. Effective pain management is essential to improve comfort and smooth the labor process. One of the non-pharmacological methods that can be used is warm compresses, which are believed to be able to reduce pain intensity through muscle relaxation mechanisms and increased blood circulation. This study aims to analyze the effect of giving warm compresses on pain levels in first-stage labor patients at Kotamobagu Regional Hospital. Method: This study used a quantitative method with a quasi-experimental design with a pretest-posttest approach with a control group. The study sample consisted of 16 respondents selected by purposive sampling. Pain measurements were taken before and after giving warm compresses using a numeric pain scale. Data analysis used the chi-square statistical test with a significance level of p <0.05. The results showed that there was a significant effect between giving warm compresses on reducing pain in first-stage labor patients with a p-value of 0.000 (p <0.05). Respondents who received warm compress intervention experienced a greater decrease in pain intensity compared to the group that did not receive the intervention. Giving warm compresses has been proven effective in reducing labor pain in the first stage. Therefore, this method can be recommended as one of the non-pharmacological pain management strategies in health care facilities. It is hoped that health workers, especially midwives, can be more active in implementing the warm compress method as part of labor pain management. In addition, further research with a larger sample size and a stronger research design is needed to strengthen these findings.